Power Consumption Of Stirred Media Mills (29e9da19-6cb3-4160-84d7-b13daaba4241) (Society for Mining, Metallurgy & Exploration, 1994)
Power consumption of stirred media mills has been studied by an approach developed from work on stirred reactors. Relationships between torque required to rotate both disc and pin impellers immersed in dense particulate media as a function of speed, impeller and tank dimensions, and other relevant variables are evaluated. Data collected during numerous different experimental conditions are analyzed. The results can be summarized and presented in the form of characteristic plots, general equations and dimensionless group correlations involving power and modified Reynolds numbers. Special attention is directed towards the rheological properties of the media, which is considered as non-Newtonian liquids and hence, the equation of power law liquids is employed. Procedure for estimating parameters of effective viscosity and scale-up guidelines with respect to power consumption are put forward.